APB & Webitors sharing session 2021 / Seng Hui Zanne - Seng, Hui Zanne (Academy of Language Studies, 2022)
APB and Webitors - the first Special Interest Group of APB have organised the 2021 sharing session virtually on the 22nd and 29th of October from 3 pm to 5 pm. The 2021 sharing session was held in two different sessions. The first session focused on the sharing of papers presented by APB members at any conference before. The second session was presented by Webitors members to share the insights related to educational technology. The objective of this sharing session is to create a platform for APB members to share their thoughts, research ideas and new knowledge. Thirteen APB members took part in this sharing session and a total of seventeen papers were presented.